Comparison of 3 Different Prothrombin Complex Concentrate Regimens for Emergent Warfarin Reversal: PCCWaR Study. Issue 8 (August 2021) - Dietrich, Scott K.; Rowe, Shaun; Cocchio, Craig A.; Harmon, Amanda J.; Nerenberg, Steven F.; Blankenship, Patrick S.
Background: The ideal dose and specific prothrombin complex concentrate (PCC) for warfarin reversal is unknown. Objective: To evaluate the reduction in international normalized ratio (INR) of 3 different PCC dosing regimens: fixed-dose activated 4-factor PCC (aPCC), fixed-dose 4-factor PCC (4PCC), and standard-dose 4PCC. Methods: This was a multicenter retrospective cohort review. Patients >18 years of age who received PCC for warfarin reversal between January 1, 2017, and December 31, 2017, were screened for inclusion. Patients were excluded if they did not receive the correct PCC dosing regimen, received PCC for nonwarfarin bleeding, had a baseline INR less than 2, or received a massive transfusion protocol. Two institutions utilized aPCC dosed at 500 IU for INR <5 and 1000 IU for INR ≥5. Two institutions utilized fixed-dose 4PCC at 1500 to 2000 units depending on patient factors. Two institutions utilized 4PCC package insert dosing. The primary outcome was achievement of post-PCC target INR ≤1.4. Secondary outcomes included percentage change in INR, lowest 24-hour INR, and mortality. Results: A total of 154 patients were included (fixed-dose aPCC: n = 29; fixed-dose 4PCC: n = 53; standard-dose 4PCC: n = 72). There was no statistical difference between groups in achieving the primary outcome (58.6% vs 69.8% vs 79.2%, respectively; P = 0.103) or any secondary outcomes. Conclusion and Relevance: There was no difference in the ability to achieve a post-PCC INR of ≤1.4 between 3 different PCC regimens for warfarin reversal. Additional research is warranted to determine the ideal dose and PCC agent for warfarin reversal.